1981
DOI: 10.1128/jcm.14.4.411-414.1981
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of the Auto Microbic system urine identification card

Abstract: The AutoMicrobic system (Vitek Systems, Inc., Hazelwood, Mo.) is a fully automated, computerized instrument. One of the most thoroughly studied aspects of the system is its ability to identify and quantify the nine most common urinary tract pathogens. The major advantages of the AutoMicrobic system are that the results of urine cultures are available in a fraction of the time required by conventional methods and that samples can be processed with fewer man-hours. Although the specificity, sensitivity, and reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Many screening methods have been proposed to detect bacteria in urine on the day of collection, both to shorten the delay inherent in the culture system and to decrease the time spent in the laboratory separating negative specimens from those considered to have significant bacteriuria. These screening tests include several manual (4,5,8,13,15,18), semiautomated (10,11,14), and automated systems (7,9,10,17).…”
mentioning
confidence: 99%
“…Many screening methods have been proposed to detect bacteria in urine on the day of collection, both to shorten the delay inherent in the culture system and to decrease the time spent in the laboratory separating negative specimens from those considered to have significant bacteriuria. These screening tests include several manual (4,5,8,13,15,18), semiautomated (10,11,14), and automated systems (7,9,10,17).…”
mentioning
confidence: 99%
“…The AMS has been shown to be an accurate, relatively rapid, cost-effective system for specimens with -105 CFU/ml and provides detection, quantitation, and identification in 4 to 9 h in a high percentage of these specimens (8,10,11,21). However, it is not cost effective for processing specimens with <105 CFU/ml (8,21).…”
Section: Discussionmentioning
confidence: 99%
“…The AMS has been shown to be an accurate, relatively rapid, cost-effective system for specimens with -105 CFU/ml and provides detection, quantitation, and identification in 4 to 9 h in a high percentage of these specimens (8,10,11,21). However, it is not cost effective for processing specimens with <105 CFU/ml (8,21). Previous investigators have suggested that by screening urine specimens with a rapid screening test such as Gram stain (8) or the Autobac system (21) and processing positive specimens on the AMS and negative specimens by conventional culture one can take advantage of the rapid automation of the AMS and make it more cost effective to use on urine specimens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations